Characteristic Features of MR Truncation Artifacts - Czervionke, Leo F.; Czervionke, Jeanne M.; Daniels, David L.; Haughton, Victor M. (American Journal of Neuroradiology, 1988)
Truncation artifacts occur in MR imaging because Fourier transforms are used to process MR signal data. These artifacts may alter the intensity, shape, and anatomic detail of structures in the spine. Ring artifacts (Gibb phenomenon) occurring near highly contrasting interfaces represent but one manifestation of truncation artifacts visible on MR images. We review truncation phenomena by providing graphic and phantom models. Ways in which truncation artifacts alter the MR appearance of the spine are discussed. We found that truncation phenomena are reduced most effectively by using a 256 × 256 matrix whenever feasible.